Strengthening Global Muslim Family Resilience: A Multidisciplinary Approach to Education, Marriage Law, and Sharia Economics in Malaysia - Lusiana Lusiana; Muhammad Sauqi; Khalilurrahman Khalilurrahman; Muhammad Syafiq (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The resilience of migrant Muslim families in Malaysia faces complex challenges, including limited access to education, legal marriage vulnerability, and economic instability. This community service research aims to strengthen family resilience through a multidisciplinary approach integrating education, marriage law, and Sharia economics. The activities were conducted from April 13–27, 2026, in Kuala Lumpur, in collaboration with the Indonesian School of Kuala Lumpur (SIKL), targeting students and parents in fostered schools. The method employed is Asset-Based Community Development (ABCD) with a descriptive-qualitative field approach. The service team involved cross-faculty student collaboration (Tarbiyah, Sharia, and Islamic Economics and Business) to provide basic literacy mentoring, legal marriage education (isbat nikah), and Sharia-based household financial management simulations. The results show significant improvements in children's literacy skills, increased parental awareness of the importance of legal documents for civil rights protection, and a shift in consumption patterns toward more planned financial management. In conclusion, interdisciplinary integration is effective in forming a